CINSARC signature as a prognostic marker for clinical outcome in sarcomas and beyond. Issue 2 (29th December 2018) - Chibon, Frederic; Lesluyes, Tom; Valentin, Thibaud; Le Guellec, Sophie
Abstract: Prognostication is a key issue for sarcoma patients' care as it triggers the therapeutic approach including chemotherapy, which is still not standard for localized patients. Current prognostic evaluation, based on the FNCLCC grading system, has recently been improved by the CINSARC signature outperforming histology‐based grading system by identifying high‐risk patients in every grade, even in those considered as low. CINSARC is an expression‐based signature related to mitosis and chromosome integrity with prognostic value in a wide range of cancers additional to sarcoma. First developed with frozen material, CINSARC is now coupled with NanoString technology allowing evaluation from FFPE blocks used in clinical practice. Consequently, CINSARC is currently evaluated in clinical trials with a dual objective of demonstrating the benefit of chemotherapy in sarcoma patients and testing its response prediction. Considering its overarching value in oncology, its development is welcome in any cancers where the prognostication needs to be improved.